Reimagining Physics Education: Addressing Student Engagement, Curriculum Reform, and Technology Integration for Learning - Verawati, Ni Nyoman Sri Putu; Nisrina, Nina (Faculty of Engineering and Applied Science, 2025)
Physics education is essential for fostering scientific literacy and critical thinking, yet it faces persistent challenges, including declining student engagement, curriculum irrelevance, and the complexities of integrating technology. This study adopts a literature review method, analyzing peer-reviewed studies published in the last five years, sourced from databases such as Scopus, Web of Science, and Google Scholar, using keywords like “physics education,” “student engagement,” and “curriculum reform.” The findings highlight that the abstract nature of physics, traditional lecture-based methods, and a lack of real-world applications contribute to reduced student interest. Addressing these issues requires the adoption of interactive, inquiry-based pedagogies and the development of contextualized curricula that align with contemporary societal challenges. Technology integration, including simulations and virtual experiments, enhances engagement but faces obstacles such as resource disparities and insufficient teacher training. Teacher preparedness remains pivotal, emphasizing professional development programs that enhance subject expertise, pedagogical skills, and technological proficiency. Additionally, educational reforms often face implementation challenges due to exam-centric systems and misalignment with classroom practices. This review advocates for a holistic approach, combining curriculum reforms, balanced technology use, and sustained investment in teacher development to revitalize physics education. By addressing these interconnected issues, physics education can become more engaging and relevant, equipping students with critical skills to navigate a technology-driven world. This work provides a foundation for future research and policy initiatives aimed at fostering inclusive and impactful physics education practices.